PENGARUH APLIKASI PUPUK KOMPOS DAN BIOCHAR TERHADAP POPULASI BAKTERI DI RIZOSFER DAN PERTUMBUHAN TANAMAN PADI GOGO (Oryza Sativa L.) - Rahmawati, Mifatun; Endang S, Lolita; Arifin, Zaenal (Department of Soil Science, Faculty of Agriculture, University of Mataram, 2024)
This reasearch to describe the effect of the application of compost and biochar on bacterial population in rhizosphere and growth of upland rice (Oryza sativa L.) This research was conducted in November-January 2021. The method used in this study was experimental by conducting experiments in greenhouse of the Faculty of Agriculture, University of Mataram. Meanwhile, the analysis of chemical and biological properties was carried out at the Chemistry and Soil Fertility Laboratory, Faculty of Agriculture, University of Mataram. The results showed that the soil used before planting was relatively less fertile (chemically). The soil used in this study had a pH value of 5.0 and available-P had 0.95 ppm, total N was 0.19%, K-exchanged was 0.22 meq/100g. In addition, the organic matter content as reflected by the C-organic value is only 1.2% which is in the low category. And the value of cation exchange capacity is in the medium category (17.43 meq/100 g of soil). administration of doses of urea and phonska fertilizer combined with the provision of compost and biochar had an effect on the variables of plant height, number of tillers and leaf width where the P1 treatment gave a significant value compared to the P0 and P2 treatments. In the parameters of root weight and stem weight, treatment P1 was more significant than treatment P0 and P2. In the total variable of microorganisms the number of bacterial colonies was significant in the P1 treatment with an average value of 7.14, in the P1 phosphate solubilizing fungus parameter it had a significant value with an average value of 3.17, in the P1 phosphate solubilizing bacteria parameter it had a significant value with an average value of 3.61 while for the respiration parameter of microorganisms p1 has a significant value with an average value of 4.36 mg C-CO2 / g soil.